Estimation of Total Carbon Stockpile and Sequestration Rates in Degraded and Non-degraded Sites of Oak and Pine Forests of Kumaun Central Himalaya - Bohra, C. S.; Jina, B. S.; Lodhiyal, L. S. (Indian Forester, 2011)
Rates at which CO2 is being sequestered in two different forest types of Himalaya was computed. For comparative study degraded and non-degraded sites of pine and oak forests in Kumaun Central Himalaya were selected. The Van Panchayats (VPs) or community forests are managing the nondegraded forest sites for centuries. It was found that the sequestration of CO2 in non-degraded forests is significantly greater than the degraded forests. On the basis of present study significance of community forests in both Uttarakhand and the world is recommended and advocated to fight against the global warming as forests ultimately become the sink for increased CO2 worldwide. The 'carbon trading' will indeed evolve as the panacea the war against global warming.